Climate change impacts on phenology and yield of hazelnut in Australia. (January 2021) - Jha, Prakash K.; Materia, Stefano; Zizzi, Giovanni; Costa-Saura, Jose Maria; Trabucco, Antonio; Evans, Jason; Bregaglio, Simone
Abstract: The growing demand for nuts and the required diversification of supply are urging to identify additional zones for hazelnut tree cultivation around the world. Given the long-term nature of the investment needed to establish new orchards, an ex-ante evaluation of the future production trends due to global changes is critical to support stakeholders and decision makers. With this motivation, we investigate the physiological response and the attainable yield of hazelnut in Australia, using a process-based model. Simulations examined phenological development, hazelnut growth processes and yield in recent past and near-future climate conditions, using an ensemble of regional climate models bounded by four global climate models (GCMs). While the entire domain of analysis will warm up in the next twenty years, the precipitation patterns are rather erratic across GCMs. The effect of climate change on hazelnut farming is variable across agro-climatic zones, except in the southeasternmost part of Australia, where all simulations agree in predicting a yield increase ranging from 18 to 52%. Elsewhere the hazelnut production potential varies, with some GCMs projecting yield increase and others estimating reductions or no significant changes. Yield increase is associated mainly with higher gross assimilation rates, whereas decrease is related to a delay in chilling requirements fulfilment, caused by the projected increase in minimum temperatures and to sub-optimal conditions for the photosynthetic process. Despite the need of additional field trials to further validate the model, these results may be used by private and public bodies to support new investment plans, and promote legislative measures aimed at encouraging hazelnut cultivation in Australia. Highlights: This study projects hazelnut yield for future using process-based modelling. Climate projections from various GCMs are used as input for the simulations. Australian temperatures are predicted to increase, while changes in rainfall is uncertain. Hazelnut yield is projected to increase in southeastern Australia in future climate. For remaining areas, future changes in yield and production are climate model-dependent.